2022
DOI: 10.3390/membranes12100922
|View full text |Cite
|
Sign up to set email alerts
|

Review of the Anti-Pollution Performance of Triple-Layer GM/GCL/AL Composite Liners

Abstract: Landfill leachates contain several types of pollutants and complex components, which pollute soils and groundwater. To compensate for the limitations of single-layer and double-layer liners, a triple-layer liner system composed of a geomembrane (GM), geosynthetic clay liner (GCL), and attenuation layer (AL) was invented and widely used in landfill anti-pollution systems. In this paper, the available literature on triple-layer GM/GCL/AL composite liners is summarized. First, the four main transport processes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 109 publications
(120 reference statements)
0
1
0
Order By: Relevance
“…The geosynthetic clay liner (GCL) is one of the most important barriers preventing the leakage of pollutants in landfills [32][33][34]. Previous studies have shown that the GCL can reduce the ground subsidence caused by garbage leakage, improve the stability of landfills and prolong the service life of landfills [35,36]. One of the main components of the GCL is bentonite particles, and the adsorption of bentonite particles is pretty large, resulting in the fact that the retention mechanism of the GCL is quite different from traditional porous media [37].…”
Section: Introductionmentioning
confidence: 99%
“…The geosynthetic clay liner (GCL) is one of the most important barriers preventing the leakage of pollutants in landfills [32][33][34]. Previous studies have shown that the GCL can reduce the ground subsidence caused by garbage leakage, improve the stability of landfills and prolong the service life of landfills [35,36]. One of the main components of the GCL is bentonite particles, and the adsorption of bentonite particles is pretty large, resulting in the fact that the retention mechanism of the GCL is quite different from traditional porous media [37].…”
Section: Introductionmentioning
confidence: 99%